DERMATOGLYPHIC, SOMATOTYPICAL AND BASIC PHYICAL QUALITIES PROFILE OF CLASSIC DANCERS FROM RIO DE JANEIRO MUNICIPAL THEATER DANCING COMPANY (Fiep Bulletin - online, 2014)
Classic ballet is an erudite modality of dance that, with its evolution, began to demand a strong physical preparation and, along with this, the necessity of a best knowledge of its practitioners. The aim of this study is to identify the basic physical qualities and the dermatoglyphic and somatotype profile of 29 dancers of the Municipal Theater of Rio de Janeiro (MTRJ), age ranging from 35,9  10,30. Dermatoglyphic characteristics (Cummins and Midlo, 1961), somatotypical characteristics (Heath and Carter, 1990) and the basic physical qualities have presented, respectively, the following results: arc (A) 4,0%, fastener (F) 44,1%, verticilo (W) 55.5%, D10 X = 15,5   2,47 SQTL X = 135,2  28,59; ectomorphy X = 3  0,58; mesomorphy X = 3,7  0,74; endomorphy X = 2,4  0,89; coordination (Test of Burpee-Mathews Donald, K. 1980) X= 6,6 rep  0,62; manual force (Dynamometry-Pitanga, Francisco, 2005): right hand X = 42,5 kg  7,55; left hand X =  43,8 kg  6,92; legs explosive force (Jump Test-Fernandes Filho, 2003) X = 56,9 cm  8,72; flexibility (goniometry-Dantas, H., 2005): shoulder abduction X = 204,6º  12,2; shoulder flexion X = 141,3º  11,03; hip flexion X = 141,3º  11,03; dorsiflexion X = 141,3º  11,03; plantar flexion X = 141,3º  11,03; hip abduction X = 141,3º  11,03. The Balance Test (stork test Donald-Mathews, K., 1980) was carried through successfully with all the subjects. Future studies are necessary so as to increase the knowledge of cassic ballet´s practitioners.
Keywords: dermatoglyphy; somatotypical; ballet; basic physical qualities